The federal budget : politics, policy, process - Schick, Allen (Brookings Institution Press, 2007)
"Updates and expands the assessment of the long-term budgetary outlook, addressing such issues as the collapse of the congressional budgetary process and the threat posed by the termination of discretionary spending caps. Concludes with a look at how the nation's deficit will affect America now and in the future"--Provided by publisher